Marital Status and Survival in Patients Diagnosed with Melanoma - J. A. Maas; A. J. Monreal; E. L. Diaz; G. Castro; P. Rodriguez de la Vega; M. Varella (Dermatology Research and Practice)
Introduction. Previous research suggests the presence of a spouse may considerably affect melanoma detection rates through more frequent examinations, better access to healthcare, and improved social support. Yet, the role of marital status on melanoma survival is currently unknown. The aim of this study is to assess whether marital status is associated with survival following melanoma diagnosis. Methods. We performed secondary analysis of data from all participants of the Florida Cancer Data System (FCDS) and included adult melanoma patients diagnosed between 2001 and 2009 with follow-up information available until 2015. Marital status was categorized as single, married, divorced, or widowed. The primary outcome was survival interval after melanoma diagnosis, which was assessed according to the time from the date of diagnosis to the time of death or last contact. Cox proportional hazard models were used to assess the independent association between marital status and survival. Results. We assessed data from 36,578 melanoma patients. Married patients were significantly more likely to survive than single patients (Hazard ratio (HR) = 0.65; 99% Confidence Interval (CI): 0.57–0.74; P<0.001) after adjusting for age, sex, race, ethnicity, geographic location, insurance status, tobacco use, primary site, stage, and histology. There was no evidence of effect modification by gender (P=0.189). Conclusions. Married patients, including both men and women, had a 35% reduction in the risk of death after melanoma diagnosis compared with single patients, and mechanisms independent of earlier detection, such as social support, may play a role in survival in patients with melanoma.